2021
DOI: 10.3233/shti210227
|View full text |Cite
|
Sign up to set email alerts
|

Designing an eHealth Coaching Solution to Improve Transitional Care of Seniors’ with Heart Failure: End-User Needs

Abstract: Based on scientific studies, heart failure is the principal cause of hospitalization among seniors. More than 50% of elderly with heart failure are readmitted to hospital within six months. Readmission is linked with poor compliance with medical treatment and recommendations, emphasizing the need for a tool to help seniors better comply with post-discharge measures. The goal of this study was to identify end-user needs for the development of a coaching solution aiming to support elderly patients but also forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…93–96 Components of telehealth that HF caregivers value include clinician communication, care coordination, record centralization, and information specifically tailored toward their loved one’s changing disease status and health care needs. 93,97,98…”
Section: Barriers To Access and Use Of Telehealth Servicesmentioning
confidence: 99%
See 3 more Smart Citations
“…93–96 Components of telehealth that HF caregivers value include clinician communication, care coordination, record centralization, and information specifically tailored toward their loved one’s changing disease status and health care needs. 93,97,98…”
Section: Barriers To Access and Use Of Telehealth Servicesmentioning
confidence: 99%
“…[93][94][95][96] Components of telehealth that HF caregivers value include clinician communication, care coordination, record centralization, and information specifically tailored toward their loved one's changing disease status and health care needs. 93,97,98 Caregivers also facilitate telehealth and remote monitoring in concrete ways. Patients with referrals are less likely to initiate HF telehealth without caregiver support, 99 and those with cognitive impairment, in particular, may benefit from the assistance of others.…”
Section: Caregiversmentioning
confidence: 99%
See 2 more Smart Citations
“…Critical gaps remain in the design and evaluation of self-management interventions, with a lack of patient and clinician involvement [ 43 ]. Rochat et al [ 44 ] emphasized the importance of iterative involvement of end users in the design and evaluation process of a coaching solution to support the postdischarge needs of patients with HF. Furthermore, the results of Fairbrother et al [ 45 ] showed that telemonitoring enhanced patients’ knowledge and understanding of their condition but that further work is required by patients and professionals to develop a shared understanding of self-management and the role and function of telemonitoring as an enabling intervention within this context.…”
Section: Introductionmentioning
confidence: 99%